Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan Prestasi Belajar Mahasiswa - Buyung Buyung; Alexon Alexon (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Student learning achievement is still low and some of the material being studied does not know its use in conducting data analysis. This study aims to describe the application of the problem based learning (PBL) model to improve student achievement in the statistical course of the Master of Educational Technology Study Program. This research method uses classroom action research. This research was conducted in the Master of Educational Technology study program in the Statistics course. The subjects of this study were first semester students in the Education Technology Master's Degree Study Program, totaling 16 people. Data collection techniques used observation sheets to assess the application of problem based learning (PBL) learning models and learning achievement tests. Data analysts use quantitative and qualitative analysis. Quantitative analysis consists of percentage, mean value and T test. While qualitative analysis uses inductive analysis by reducing data, presenting data and drawing conclusions. The results showed that the application of the problem based learning model could improve the statistical learning achievement of students of Master of Education Technology. This result implies that if the lecturer wants to improve student statistical learning achievement, then apply the Problem Based Learning learning model in the learning process.